Entrepreneurship education in tourism : a study on the institutions of higher education in Finland - Deininger, Bianka (2020)
Entrepreneurship is an important driver in creating new jobs and contributing to a growing economy – and so is the highly versatile and complex tourism industry. Therefore, it is presumed, that entrepreneurial thinking and acting tourism professionals may bring an even greater value to a local economy. Therefore, this thesis strives to illuminate on the origins of entrepreneurial acting individuals in the respective industry. An extensive literature review is carried out to reveal, that teaching for and about entrepreneurship in institutions of higher education is key to developing desired skills and knowledge. Entrepreneurship in the tourism industry has been subject in the literature several times, even within the chosen geographical context of this thesis, Finland. However, researchers so far failed to address it within an educational context. Therefore, this paper describes an exploratory research study aimed at evaluating the effectiveness of integrating an entrepreneurship courses or modules within tourism education programs of higher education institutions in Finland. To do so, the students themselves are surveyed on their entrepreneurial attitudes, their subjective opinions on their own control over their entrepreneurial behaviour as well as the perceived opinion of their personal environment towards entrepreneurship. These three factors are understood to be influenced by entrepreneurial education and will lead towards the intention to act entrepreneurial and eventually carry out entrepreneurial behaviour. The results show an overall satisfactory output, as entrepreneurial attitude as well as the perceived behavioural control can explain partially the entrepreneurial intentions of tourism students in Finland. However, the subjective norm seems to not contribute to a future entrepreneurial behaviour as expected.